Publicandum (s.n., 1797)
Wyznaczenie ścisłych terminów zmiany służby
Not. rkps.: "Exempl. für Richtowo"
Keywords: Prawodawstwo; Prusy; Polska; Służba prawodawstwo 18 w. Prusy; Służba prawodawstwo 18 w. Polska